Perlindungan Hukum Preventif dalam Menjamin Hak-Hak Tenaga Kerja Menurut Perjanjian Kerja Berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The purpose of this study is to examine the implementation of employment agreements as one of the means of providing legal protection for workers’ rights. The research method employed in this study is normative juridical, utilizing primary and secondary legal materials obtained through the analysis of statutory regulations, legal scholars’ opinions, as well as books and journals relevant to the subject under study. The results of the study indicate that employment agreements, as a form of preventive legal protection for workers’ rights, are a consequence of the application of the welfare state concept, thereby requiring the state to intervene in employment relationships arising from such agreements. This form of intervention can be observed in Law Number 13 of 2003 concerning Manpower. The provisions contained in this law, particularly Article 54 paragraph (1) of Law Number 13 of 2003 concerning Manpower, constitute a form of preventive legal protection, especially in points (e) and (f), as they regulate economic rights as well as the rights and obligations of workers. These provisions provide protection and serve as a form of legal certainty that safeguards workers from the beginning of their employment. The obstacles encountered in the implementation of employment agreements as a preventive means of protecting workers’ rights are divided into three factors: regulatory factors, legal culture factors, and legal structure factors.